2021
DOI: 10.1002/mdc3.13331
|View full text |Cite
|
Sign up to set email alerts
|

Anti Zic4 Paraneoplastic Neurological Syndrome Presenting as Oscillopsia

Abstract: Video 1. The video shows patient with bilateral gaze-evoked nystagmus, normal saccades, broken pursuits and impaired inhibition of vestibulo-ocular reflex (abnormal pursuit to either side as the subject is rotated while looking at a target that is also being rotated), subtle left upper limb dysmetria, and mild gait ataxia with impairment in tandem gait. The gait unsteadiness is subjectively better when walking with eyes closed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…In the largest case series of 61 patients, it has been shown that patients with isolated Zic4 antibodies are most likely to develop cerebellar dysfunction 6 . Autonomic instability with a rhombencephalitis like presentation in anti‐Zic4 has been previously described by Loehrer et al 7 Report of abnormal VOR suppression with oscillopsia in anti‐Zic4 associated neurological disorder is also there in literature 8 . Our patient had additional behavioral symptoms in addition to autonomic and cerebellar symptoms.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the largest case series of 61 patients, it has been shown that patients with isolated Zic4 antibodies are most likely to develop cerebellar dysfunction 6 . Autonomic instability with a rhombencephalitis like presentation in anti‐Zic4 has been previously described by Loehrer et al 7 Report of abnormal VOR suppression with oscillopsia in anti‐Zic4 associated neurological disorder is also there in literature 8 . Our patient had additional behavioral symptoms in addition to autonomic and cerebellar symptoms.…”
Section: Discussionsupporting
confidence: 67%
“…6 Autonomic instability with a rhombencephalitis like presentation in anti-Zic4 has been previously described by Loehrer et al 7 Report of abnormal VOR suppression with oscillopsia in anti-Zic4 associated neurological disorder is also there in literature. 8 Our patient had additional behavioral symptoms in addition to autonomic and cerebellar symptoms. There was no complaint of oscillopsia.…”
Section: Discussionmentioning
confidence: 63%